Logistics Cost Analysis of Catfish in Special Region of Yogyakarta, Indonesia: Internal and External of Logistics Component Costing Systems - Sylvia, Teny; Widodo, Kuncoro Harto; Ismoyowati, Dyah (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2023)
Catfish are the most popular cultivated fish in special region of yogyakarta in special region of yogyakarta especially Sleman, Kulon Progo, and Bantul District.  These products are categorized as high perishable product so need a special handling to keep the quality from fish farmers to the customers. The aims of this study are to identify and calculate the logistics cost component that needed to keep the quality along the supply chain of catfish. There are three types of data collection methods used, namely observation, in- depth interview, and literature review. The analysis includes descriptive analysis, logistics cost components using ABC, and cost charging systems. Furthermore, it can be known the proportion of each logistics cost component of catfish. This study shows that there are six component of catfish logistics cost, i.e. procurement, material handling, transportation, maintenance, inventory, and customer communication. It also shows that the highest logistics cost component averaged proportion is, 76.421%, material handling.